CLINICAL EFFICACY OF AYURVEDIC TREATMENT REGIMEN IN THE MANAGEMENT OF KASHTARTAVA (PRIMARY DYSMENORRHEA) – A RANDOMIZED CONTROLLED CLINICAL TRIAL - Kamini Dhiman (International Journal of Drug Delivery Technology, 2026)
Background: Dysmenorrhoea refers to the pain associated with menstruation, typically occurring in the lower abdomen or pelvis. The intensity of pain can vary from mild to severe, and in some cases, the discomfort is debilitating enough to interfere with daily activities, including work and school attendance. Kashtartava (painful menstruation/primary dysmenorrhea) in Ayurvedic terms is characterized by painful menstrual cramps and is often associated with Vata dosha (bio-energetic force responsible for movement) imbalance. Objective: To evaluate the clinical efficacy and safety of Kuberaksha Vati combined with Dashmoola Taila Matra Basti (medicated oil enema) in managing primary dysmenorrhea compared with conventional pharmacotherapy. Methods: A prospective, randomized, open-label, double-arm clinical trial was conducted at XXXXXX. A total of 205 patients aged 15–24 years with primary dysmenorrhea were enrolled. Group A (102 patients) received Kuberaksha Vati (1 g three times daily) and Dashmoola Taila Matra Basti (60 ml per rectal route for 7 days after menstruation) for 3 months, while Group B (103 patients) received Mefenamic acid (500 mg) and Dicyclomine hydrochloride (20 mg) as needed. Primary outcome measures were pain intensity (Visual Analog Scale, VAS) and pain duration. Secondary outcome measures focused on associated symptoms (MDQ, VMS), quality of life (SF-36), and consumption of analgesic. Safety was assessed via laboratory investigations. Results: Significant improvements were observed in pain intensity (VAS: 2.98 to 0.83) and pain duration (2.20 to 0.15) in Group A compared to Group B (VAS: 2.84 to 2.42, pain duration: 2.53 to 2.32). Group A showed better improvements in associated symptoms, quality of life (SF-36 scores), and analgesic consumption. Both treatments were well-tolerated, with no severe adverse effects reported. Conclusion: Ayurvedic treatment regimen of Kuberakshadi Vati and Dashmoola Taila Matra Basti proved more effective than conventional pharmacological treatments in managing primary dysmenorrhea. Clinical Trial Registry of India (CTRI/2020/07/026892)